Variabilidade espacial de atributos químicos em um Argissolo sob pastagem - de Souza, Gustavo Soares; de Souza Lima, Juliao Soares; Silva, Samuel de Assis; de Oliveira, Rone Batista (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
Studies show the importance of knowing the variability of soil attributes for a more efficient management. This work was carried out to evaluate the spatial variability of the chemical attributes of an Ultisol, cultivated with Brachiaria decumbens pasture in Alegre - ES. Soil samples were collected at a depth of 00-0.2 m, at the crossing points of a regular grid with 10 m-intervals, comprising a total of 64 points. Data were submitted to descriptive statistics, geostatistics and kriging interpolation analysis. The coefficient of variation was low for pH, high for Al and m%, and medium the other attributes. The attributes pH, P, H+Al and m% presented strong dependence, and the other moderate dependence. The attributes presented a spatial dependence structure, allowing their mapping by geostatistics techniques.
Spatial variability of chemical attributes in an Ultisol under pasture
Keywords: spatial dependence; geostatistics; kriging